Hope, agency, and adolescents' sexual and reproductive health: A mini review - Groenewald, Candice; Isaacs, Nazeema; Qoza, Phiwokazi (Frontiers in Reproductive Health, 2023)
Availability of and access to services that promote sexual and reproductive health (SRH) amongst adolescent girls have become a global priority. Yet, while researchers have explored the factors that influence uptake of SRH services in low-and-middle income countries, the role of hope and agency in accessing SRH services is less understood. In this mini review we explore how these factors influence adolescents SRH and access to SRH services. A systematic search was conducted across three databases including EBSCO-host web, Pubmed and SA epublications, a database of Africa-focused journals. To ensure inclusivity of a wide range of articles, we made use of Boolean phrase options within the databases for the keywords ‘hope’ and ‘agency’. Our review found no studies that focused on hope and its role in adolescent SRH or seeking SRH services. However, the literature revealed the complexities of adolescent SRH agency and autonomy where female adolescents had limited autonomy to make SRH decisions. Limited access to adolescent friendly SRH services was also found to restrict girls’ agency to prevent unintended pregnancies or to take up SRH support. This paper contributes to knowledge by synthesising the literature the role of hope and agency in accessing SRH services amongst adolescents. Given the paucity of research, empirical studies are needed to further understand the extent to which hope, agency and other subjective factors implicate adolescent SRH in the African context.